2020
DOI: 10.1145/3392837
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Conversational Styles in Conversational Microtask Crowdsourcing

Abstract: Crowdsourcing marketplaces have provided a large number of opportunities for online workers to earn a living. To improve satisfaction and engagement of such workers, who are vital for the sustainability of the marketplaces, recent works have used conversational interfaces to support the execution of a variety of crowdsourcing tasks. The rationale behind using conversational interfaces stems from the potential engagement that conversation can stimulate. Prior works in psychology have also shown that conversatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Our experimental findings revealed that workers with specific conversational styles have significantly higher output quality, higher user engagement and less cognitive task load while they are completing a difficult task, and have less task execution time in general. The findings have important implications on worker performance prediction and quality-aware task scheduling in microtask crowdsourcing [3].…”
Section: Analyzing Conversational Styles and Workers Performancementioning
confidence: 93%
See 1 more Smart Citation
“…Our experimental findings revealed that workers with specific conversational styles have significantly higher output quality, higher user engagement and less cognitive task load while they are completing a difficult task, and have less task execution time in general. The findings have important implications on worker performance prediction and quality-aware task scheduling in microtask crowdsourcing [3].…”
Section: Analyzing Conversational Styles and Workers Performancementioning
confidence: 93%
“…This demo is presented for the system described in our previous work [3]. The code is available online for the benefit of the community (https://github.com/qiusihang/ticktalkturk).…”
Section: Introductionmentioning
confidence: 99%
“…We will compare conversational crowdsourcing with the traditional web-based microtask crowdsourcing to explain the advantages of conversational crowdsourcing in terms of increasing user satisfaction, improving user engagement, and decreasing perceived workload [15,20]. Next, we will explain the effect of using different conversational styles [27,28], and share empirical insights into how we can define a conversational style, how to estimate the conversational style, and how to exploit the conversational style to facilitate an effective task design [19]. Finally, we will showcase conversational crowdsourcing in a variety of domains, such as supporting microtask execution and aiding informational web search [22].…”
Section: Cuis For Crowd Computingmentioning
confidence: 99%
“…It was found that crowd workers exhibited an overall satisfaction while working with the chatbot, and the results produced were of a better quality compared to the web interface (Mavridis et al 2019). Others studied the impact of different conversational styles employed in a text-based conversational agent on the worker performance and engagement, and proposed models to estimate the conversational styles of workers (Qiu, Gadiraju, and Bozzon 2020a;2020b). Results indicated that conversational agents with different conversational styles did not impact the output quality, but they had positive effects on worker engagement and worker retention.…”
Section: Crowd-powered Conversational Interfacesmentioning
confidence: 99%